Worried about being imperfect? The mediating effect of physical appearance perfectionism between Instagram addiction and body esteem. (February 2022) - Simon, Patricia D.; Cu, Sydney Margaret O.; De Jesus, Kim Elizabeth M.; Go, Nicole Therese S.; Lim, Keena Tracy F.; Say, Chloe Louise C.
Abstract: Physical appearance is an important domain wherein people tend to have perfectionistic tendencies. Physical appearance perfectionism is a domain-specific type of perfectionism that has a potential role to play in how addiction to popular social media platforms such as Instagram can negatively impact a person's body esteem. To test the hypothesis that physical appearance perfectionism mediates the relationship between Instagram addiction and body esteem, data were collected from 902 undergraduate students from the Philippines. While there were gender differences in the levels of the variables, analysis showed that physical appearance perfectionism (worry about imperfection) significantly mediates the relationship between Instagram addiction and body esteem even after controlling for the effects of sex. This confirms the importance of studying how individual difference variables such as physical appearance perfectionism can explain why social media has a significant influence on how people perceive their physical bodies. Future research that tests the effects of Instagram addiction and physical appearance perfectionism on psychological outcomes other than body esteem is recommended to better inform the design of interventions for the prevention of addictive behaviors and potentially pathological traits. Highlights: Gender differences in Instagram addiction, physical appearance perfectionism, and body esteem were found. Worry about imperfection mediates the relationship between Instagram addiction and body esteem. This mediating effect is maintained even after the effect of gender is controlled.